Design and development of automatic voltage regulator using Ziegler-Nichols PID for electrical irons testing - Sukma, Irawan; Suseno, Aji Dwi; Muhidin, Muhidin; Bakti, Prayoga; Ardiatna, Wuwus; Supono, Ihsan; Firdaus, Himma; Mandaris, Dwi (Institute of Advanced Engineering and Science, 2024)
This research presents an automated voltage regulation system crucial for a power input test of electric irons based on SNI IEC 60335-2-3 clause 11.4. The system is designed with an Arduino-based proportional-integral-derivative (PID) control mechanism to augment voltage stability and meet the standard requirement. The system comprises a microcontroller for PID control, a dimmer as the actuator, and a voltage sensor for error measurement. It utilizes the Ziegler-Nichols (Z-N) oscillation method to determine the PID control parameters. The simulation results identified a third-order transfer function as the best fit for the system, and the optimal PID parameters for the system are Kp=60, Ki=125, and Kd=500. The system was tested under the electric iron's active and non-active conditions. The proposed PID system demonstrated stable responses, effectively regulating the system voltage with minimal overshoot and settling time, and meeting standard requirements even under varying load conditions. It suggests potential applications beyond electric iron testing, promising efficiency improvements in broader household product testing.